Bleach. 64, Death in vision - Kubo, Tite (VIZ Media, LLC, 2015)
"As the battle between the Soul Reapers and Quincies continues to heat up, both sides start experiencing casualties. Yachiru now joins the battlefield and prepares to show her true powers for the first time. However, standing in her way is an opponent whose abilities may defy imagination" --